Large‐Scale Bottom‐Up Fabricated 3D Nonlinear Photonic Crystals - Viola Valentina Vogler‐Neuling; Ülle‐Linda Talts; Rebecca Ferraro; Helena Weigand; Giovanni Finco; Joel Winiger; Peter Benedek; Justine Kusch; Artemios Karvounis; Vanessa Wood; Jürg Leuthold; Rachel Grange (Advanced Photonics Research)
Nonlinear optical effects are used to generate coherent light at wavelengths difficult to reach with lasers. Materials periodically poled or nanostructured in the nonlinear susceptibility in three spatial directions are called 3D nonlinear photonic crystals (NPhCs). They enable enhanced nonlinear optical conversion efficiencies, emission control, and simultaneous generation of nonlinear wavelengths. The chemical inertness of efficient second‐order nonlinear materials (χ(2)) prohibits their nanofabrication until 2018. The current methods are restricted to top‐down laser‐based techniques limiting the periodicity along the z‐axis to 10 μm. The first bottom‐up fabricated 3D NPhC is demonstrated in sol–gel‐derived barium titanate by soft‐nanoimprint lithography: a woodpile with eight layers and periodicities of 1 μm (xy‐plane) and 300   nm (z‐plane). The surface areas exceed 5.3×104 μm2, which is two orders of magnitude larger than the state‐of‐the‐art. This study is expected to initiate bottom‐up fabrication of 3D NPhCs with a supremely strong and versatile nonlinear response.